A Salvage Operation for Total Penis Amputation Due to Circumcision - Bilsev Ince; Ayse Ozlem Gundeslioglu (Archives of Plastic Surgery, 2013)
Circumcision is one of the most common rituals in Jewish and Islamic cultures. It may also be performed for phimosis correction or the treatment of recurrent balanitis. Although circumcision is considered to be a technically easy and safe surgical procedure with no significant risk, it may lead to severe complications such as necrotizing fasciitis or total penis amputation. In this report, we present a case of penis amputation at two levels occurring with third-degree burns due to electrocautery during circumcision. Although penile replantation was attempted, it was unsuccessful due to burn damage to the veins. After restoration of the functional structures, the penis was buried in the inguinal area by reepithelization to maintain blood circulation. The recovery of the penis was successful. This case is presented as a novel example of groin flap surgery to achieve a functionally and aesthetically acceptable outcome in a salvage operation for a penis with significant traumatic injury, which has not been previously reported in the literature.